Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/270953
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Scar after Total Thyroidectomy: A Single Blinded Randomized Trial Comparing Octyl-Cyanoacrylate and Subcuticular Absorbable Suture

Abstract: Objective. To compare the quality of resulting scar at 6 weeks after total thyroidectomy with the use of the tissue adhesive octyl-cyanoacrylate or subcuticular absorbable suture for the closure of cervicotomy. Material and Methods. There are 50 patients undergoing a cervicotomy for total thyroidectomy. Twenty-five patients were randomly assigned to closure with tissue adhesive and 25 with subcuticular absorbable suture. At week 6 the scar was evaluated by blinded assessors with the Italian version of POSAS qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 32 publications
3
44
1
Order By: Relevance
“…The observed difference between the OSAS and the PSAS score is in agreement with some recurrent findings of the literature, which tend to undervalue the influence of the subject's satisfaction, compared to trained evaluator assessment [15]. This is due to the fact that the individuals assessed their striae in a highly subjective, various, and difficult to capture way, resulting in a weak intersubjective comparability of judgments.…”
Section: Discussionsupporting
confidence: 88%
“…The observed difference between the OSAS and the PSAS score is in agreement with some recurrent findings of the literature, which tend to undervalue the influence of the subject's satisfaction, compared to trained evaluator assessment [15]. This is due to the fact that the individuals assessed their striae in a highly subjective, various, and difficult to capture way, resulting in a weak intersubjective comparability of judgments.…”
Section: Discussionsupporting
confidence: 88%
“…One paper by Guarino et al was a retrospective cohort study. Three studies compared staples vs glue; three papers compared sutures vs staples; two papers compared suture vs steri‐strips; and two papers compared sutures vs glue . A total of 742 patients were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to surgical procedure, all but one, Vinay et al, included a description of the procedure performed, although to varying detail. Five papers described platysma closure, and four papers described subcutaneous closure prior to skin/epidermal closure. Pronio et al reported the use of ceftriaxone as prophylactic antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observer-based ratings have been used elsewhere to evaluate thyroidectomy scar aesthetics without making a comparison to other approaches and to compare alternative methods of skin closure. [26][27][28] Another potential source of error in prior studies is having raters assess scars with no frame of reference. Without a frame of reference, a rater may judge a scar to be favourable or unfavourable that they would judge differently if they were aware that other potential scars were possible.…”
Section: Discussionmentioning
confidence: 99%